Transcription factor TFII-I fine tunes innate properties of B lymphocytes - Singh, Amit; Kaileh, Mary; De, Supriyo; Mazan-Mamczarz, Krystyna; Bayarsaihan, Dashzeveg; Sen, Ranjan; Roy, Ananda L. (Frontiers in Immunology, 2023)
The ubiquitously expressed transcription factor TFII-I is a multifunctional protein with pleiotropic roles in gene regulation. TFII-I associated polymorphisms are implicated in Sjögren’s syndrome and Lupus in humans and, germline deletion of the Gtf2i gene in mice leads to embryonic lethality. Here we report a unique role for TFII-I in homeostasis of innate properties of B lymphocytes. Loss of Gtf2i in murine B lineage cells leads to an alteration in transcriptome, chromatin landscape and associated transcription factor binding sites, which exhibits myeloid-like features and coincides with enhanced sensitivity to LPS induced gene expression. TFII-I deficient B cells also show increased switching to IgG3, a phenotype associated with inflammation. These results demonstrate a role for TFII-I in maintaining immune homeostasis and provide clues for GTF2I polymorphisms associated with B cell dominated autoimmune diseases in humans.